CLONING OF CHIA FROM SERRATIA MARCESCENS AND ITS EXPRESSION IN E. COLI - MALIK AHMED PASHA; ARSHIANAAZ BELGAUMWALA; P. U. KRISHNARAJ; M. S. KURUVINASHETTI (The Bioscan, 2015)
Six best isolates of Serratia marcescens were selected for studying variant of chiA by ARFLP method. Except AUDS170chiA, chiA from other isolates showed similar (but different from sm141chiA) profile with PstI. Full length sequence analysis of AUDS096chiA and AUDS106chiA showed 97.40% and 97.34% similarity with sm141chiA. The expression profile based on SDS PAGE and hydrolysis of colloidal chitin proved chiA from AUDS106 is the best. In-silico analysis of sequence revealed that most of variants in the genes are at wobble position which does not alter the amino acid they code. But the variations in AUDS096chiA changed the GC content (54.72% to 66.03%) leading to reduced translational efficiency in E. coli. The variant of gene from different isolates may vary in function to a larger extent and hence classification of isolate from less to more potent.